Implementation method for enterprise-class mapping knowledge domain search engine on the basis of electric power specialty lexicon - CHEN DA; HU YONG; WU YANQING (2018)
The invention discloses an implementation method for an enterprise-class mapping knowledge domain search engine on the basis of an electric power specialty lexicon, and relates to the field of the enterprise-class mapping knowledge domain search engine. The mapping knowledge domain construction and search, which takes equipment as a core, of power grid full business domain knowledge can be realized, the isolation of search contents is solved through the mapping knowledge domain, and the uniform portal search of the full subject domain data of power grid equipment is realized. The method is used for realizing the mapping knowledge domain construction of the power grid full subject domain and a mapping knowledge domain search engine, the problem that an existing power grid monitoring information data size is large and efficiency for obtaining effective mechanism information is low is solved, the flat operation and maintenance of data assets is realized, and the value of the data assets is performed. 基于电力专业词库的企业